Wage cyclicalities and labor market dynamics at the establishment level: Theory and evidence - Christian Merkl; Heiko Stüber (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institute for Economics, 2016)
This paper analyzes the effects of different wage cyclicalities on labor market flow dynamics at the establishment level. We derive a model that allows for heterogeneous wage cyclicalities across firms over the business cycle and confront the theoretical results with the new AWFP dataset, which comprises the entire universe of German establishments. In line with theory, establishments with more procyclical wage movements over the business cycle have a more countercyclical hires rate and employment behavior. This result is robust when we look at certain sectors and states. Wage cyclicalities do not only have the expected qualitative impact on stocks and flows, but the quantitative responses are also in line with the proposed model. More generally, our empirical results provide support for theories that lead to an effect of wage rigidities on labor market flow dynamics.
Keywords: E24; E32; J64; 330; Labor Market Flows; Wages; Administrative Data; Establishment; Matches